Constraints on TESS albedos for five hot Jupiters. Issue 3 (9th April 2022) - Blažek, Martin; Kabáth, Petr; Piette, Anjali A A; Madhusudhan, Nikku; Skarka, Marek; Šubjak, Ján; Anderson, David R; Boffin, Henri M J; Cáceres, Claudio C; Gibson, Neale P; Hoyer, Sergio; Ivanov, Valentin D; et al.
ABSTRACT: Photometric observations of occultations of transiting exoplanets can place important constraints on the thermal emission and albedos of their atmospheres. We analyse photometric measurements and derive geometric albedo ( A g ) constraints for five hot Jupiters observed with TESS in the optical: WASP-18 b, WASP-36 b, WASP-43 b, WASP-50 b, and WASP-51 b. For WASP-43 b, our results are complemented by a VLT/HAWK-I observation in the near-infrared at $2.09\, μ$ m. We derive the first geometric albedo constraints for WASP-50 b and WASP-51 b: A g < 0.445 and A g < 0.368, respectively. We find that WASP-43 b and WASP-18 b are both consistent with low geometric albedos ( A g < 0.16) even though they lie at opposite ends of the hot Jupiter temperature range with equilibrium temperatures of ∼1400 K and ∼2500 K, respectively. We report self-consistent atmospheric models that explain broad-band observations for both planets from TESS, HST, Spitzer, and VLT/HAWK-I. We find that the data of both hot Jupiters can be explained by thermal emission alone and inefficient day–night energy redistribution. The data do not require optical scattering from clouds/hazes, consistent with the low geometric albedos observed.